Mineralogia e magnetometria de solos roraimenses - Araújo, Albanira Cordeiro de (2012)
Diffraction ray X (process measurement of X ray diffraction) and magnetometry (process measurement of the magnetization) were used as experimental techniques to increase knowledge of the soils of Central Roraima: Soil samples were collected near the Nova Olinda mountain range and Belo Horizonte ranch (regions of Boa Vista Formation outcrops influenced by the Apoteri Formation) in the neighborhood of Serra do Tucano (training Boa Vista region with strong influence of the Formation outcrops Tucano and Apoteri mountain range) in the region of Amajari (Cauarane formation group) and samples in the region of Mucajai (Mucajai formation). The soils showed a predominance of iron oxides: hematite, goethite, maghemite and magnetite. Also non-ferrous minerals were identified as kaolinite, quartz. The average diameter of the crystals, the kaolinite was estimated as a function of soil depth collected. Through the magnetization curves of samples of concentrated magnetic fields magnetic classify soils that showed spontaneous magnetization in two groups: multiple domain (MD) and pseudo-single domain (PSD).